Palace of Horticulture (Pacific Novelty Co.)
On verso: The building is surmounted by a huge glass dome larger than that of St. Peter's, Rome. At night it is illuminated from within by means of searchlight projectors so arranged that the half sphere seems to be a mass of light demons.